1979
DOI: 10.4315/0362-028x-42.9.735
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Micro-ID, Minitek and Conventional Methods with Enterobacteriaceae Freshly Isolated from Foods

Abstract: A total of 400 Enterobacteriaceae isolates freshly taken from broiler carcasses, ground beef, pork sausage, raw shrimp, pre-wrapped sandwiches, raw carrots, lettuce and fresh strawberries was inoculated into the 15 biochemical tests of the Micro-ID (4-h) system and into the 15 corresponding tests in the Minitek (24-h) and conventional systems. For each food there were 750 biochemical test comparisons (50 isolates × 15 tests). The overall agreement between Micro-ID and conventional tests was 96.8%, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…When muscle of pH 5.4 to 5.55 was stored for 15 days, S. liquefaciens attained counts on the meat in the polythene, nylon, and EVA/PVDC packs of 107 to 108, 2 x 106 to 5 x 106, and 105 CFU/cm2, respectively. When microbial growth had reached stationary phase (21 to 24 days), the viable counts on the meat in the polythene, nylon, and EVA/PVDC packs were about 108, 3 x 107, and 106 CFU/cm2, respectively. On the other hand, meat of this pH (5.4 to 5.55) vacuum packed in Al-foil showed no evidence of growth during 24 days of storage at 50C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When muscle of pH 5.4 to 5.55 was stored for 15 days, S. liquefaciens attained counts on the meat in the polythene, nylon, and EVA/PVDC packs of 107 to 108, 2 x 106 to 5 x 106, and 105 CFU/cm2, respectively. When microbial growth had reached stationary phase (21 to 24 days), the viable counts on the meat in the polythene, nylon, and EVA/PVDC packs were about 108, 3 x 107, and 106 CFU/cm2, respectively. On the other hand, meat of this pH (5.4 to 5.55) vacuum packed in Al-foil showed no evidence of growth during 24 days of storage at 50C.…”
Section: Resultsmentioning
confidence: 99%
“…Psychrotrophic members of the Enterobacteriaceae family are frequently found on fresh meats (6, 13), and particularly on vacuum-packaged meats (1,22). Serratia liquefaciens appears to be detected more frequently and in greater numbers than other members of the Enterobacteriaceae (3,5,14,16,18,19,22). Yersinia enterocolitica has been found on vacuum-packaged beef and lamb (10,12,21,22) and in ground beef (3), Enterobacter cloacae has been found on vacuum-packaged lamb (19) and in ground meat (13), and Aeromonas spp.…”
mentioning
confidence: 99%
“…It has been demonstrated that the types of competing bacteria present may affect the recovery of Salmonella and that these are an important factor to consider in selecting the most effective enrichment media (Hugues et al, 1978;Bailey et al (1981). E. coli are normally present in the chicken gut in large (Cox et al, 1975(Cox et al, , 1979. This organism may, thus, be present in high numbers on some of the material entering the rendering plant.…”
Section: Resultsmentioning
confidence: 97%
“…Enterobactericeae prevalent among the isolates chosen for identification and in order of decreasing magnitude were: Enterobacter cloacae, Escherichia coli, Enterobacter agglomerans, Hajizia alvei, Klebsiella oxytoca, Serratia rubidaea, and Citrobacter fieundii. These organisms are found frequently in soil and have been found previously on raw fruits and vegetables and do not usually represent a public health concern (Cox et al 1979;Senter et al, 1984).…”
Section: Microbialmentioning
confidence: 97%